Effect of a Nursing Care Program Based on King’s Theory of Goal Attainment on the Self-efficacy of Diabetic Patients - Delshad Shahmohammadi; Seyedeh Narjes Mousavizadeh; Mahnaz Ilkhani; Malihe Nasiri; Mahtab Sattari (Journal of Holistic Nursing and Midwifery)
Introduction: In managing diabetes, the self-efficacy of patients for self-care and adherence to treatment is important. One of the nursing theories that can lead to patients’ participation in care is King’s theory of goal attainment. Objective: This study aims to investigate the effect of a nursing care program based on the theory of goal attainment on the self-efficacy of patients with diabetes. Materials and Methods: This quasi-experimental study was conducted on 60 patients with type 2 diabetes admitted to the endocrinology departments of two hospitals in Tehran, Iran. They were randomly assigned to two intervention (n=30) and control (n=30) groups. The data were collected using a sociodemographic/clinical form, the diabetes management self-efficacy scale (DMSES), and the goal attainment scaling (GAS). The intervention group received the nursing care program based on King’s theory. The self-efficacy of the patients was measured before, two weeks after (post-test), and two months after (follow-up) the intervention. Chi-square, paired t-test, independent t-test, and repeated measures ANOVA were used for data analysis. Results: Most of the participants were female (68%) and married (71%), and illiterate (30%) in the age group of 51-60 years (43%). Before the intervention, the DMSES score was 144.10±14.13 in the intervention group and 139.63±13.46 in the control group. Two weeks after the intervention, the scores were 162.26±8.97 and 137.36±13.29, respectively. Two months after the intervention, the scores were 166.5±8.16 and 136.96±11.8, respectively. There was a statistically significant difference in the two groups in the post-test and follow-up phases, compared to the pre-test phase (P=0.001). The difference was also significant between the two groups after intervention (P=0.001). According to repeated measures ANOVA results, the effect of time (P=0.001, η2=0.438) and the interaction effect of time and group (P=0.001, η2=0.538) in the intervention and control groups were significant. Conclusion: The nursing care program based on the theory of goal attainment can improve diabetic patients’ self-efficacy two weeks and two months after implementation. The theory of goal attainment can be used in care programs for diabetic patients.